Identity and social transformation - Ryder, John, 1951-; Šíp, Radim. (Value Inquiry Book Series, 2011)
This book is the fifth volume of selected papers from the Central European Pragmatist Forum (CEPF). The CEPF was founded in 2000 to provide an opportunity for American and European specialists in American philosophy to share their work with one another and to develop an understanding of the contemporary applications of the American philosophical traditions. The current volume deals with the general questions of identity and social transformation. Papers are organized into sections on the Transformation of Pragmatism, Metatheoretical conditions for Identity Transformation, the Fluidity of Identity, Transforming Self, Transforming Society, Art and Transformation, Richard Rorty on the Transformation of Society and Self, and Pragmatism and Central Europe. The authors are among the leading specialists in American philosophy from universities across the US and in Central and Eastern Europe. In their papers the authors address a range of topics, including comparative analyses of American philosophical figures with prominent representatives of other philosophical traditions, contemporary issues in ethics, aesthetics and social philosophy, unresolved problems in American philosophy, and issues of contemporary policy. All papers deal in one way or another with the general theme of identity and transformation, individual and social.